SIMBOLISME KEBUDAYAAN TIONGKOK DALAM FILM NORTHEAST FOLKTALES KARYA JI YIDA: ANALISIS SEMIOTIKA - Indri Amsalta Anakampun (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study examines the cultural and mythological symbolism in Ji Yida’s film Northeast Folktales as a reflection of the belief system of Chinese society. The analysis employs Roland Barthes ’ semiotic framework, which encompasses three levels of meaning: denotation, connotation, and myth. The aim of this research is to explore how visual and narrative elements represent local mythology, including the five Wudaxian deities, ritual practices, and supernatural figures as components of cultural identity. Using a qualitative descriptive method, the study analyzes scenes, symbols, and dialogues to identify the relationship between signs and cultural meanings. The research results obtained were 10 (ten) data which showed that there were symbols of sacred animals, offering rituals, and representations of supernatural beings which functioned as cultural communication media which depict the relationship between society and the spirit world. Roland Barthes ’ semiotic analysis shows that each sign conveys denotative meanings rooted in folkloric traditions, connotative meanings that express emotional and social values, and mythic structures that reinforce the spiritual identity of Northeast Chinese communities. Overall, Northeast Folktales effectively represents the richness of folklor  and mythology that continues to live within the collective memory of society.